Survey of interest of model terpadu madani palu elementary school students in softball - Fajri, Khairil; Tri Putra Nur Ikhsan, M; Ismail, Muhammad; Sardiman; Saldi, Muh.; Lumbaa, Krisyanto Batong; Daipaha, Moh. Tris Maulana (Jorpres (Jurnal Olahraga Prestasi), 2025)
This study aims to find out how much interest students are in softball, especially in SD Model Terpadu Madani Palu. This study is a type of descriptive research with the aim of finding out how high the interest of SD Model Terpadu Madani Palu students is in softball. With the method used is a survey, which is a study that takes samples from one population with a data collection technique using a questionnaire/questionnaire, the population in this study is all students in grades IV, V, and VI of SD Integrated Model Madani Palu which totals 220 while the sample is selected among the population according to the researcher's desire which amounted to 45 students or 20 percent of the existing population. The scores obtained from the questionnaire were then analyzed using quantitative descriptive analysis expressed in the form of percentages. The results of this study show that students' interest in participating in softball extracurricular sports at SD Model Terpadu Madani Palu is moderate with a percentage of 35%. Meanwhile, the interest of other students in the very high category was 3 students or 7%, the high category was 10 students or 22%, the low category was 13 students or 29%, and the very low category was 3 students or 7%. Schools must be able to stimulate students' interests in their potential, based on factors that affect students' interest in achievement. Keywords: Interest, Coaching, Students, Softball